Pengaruh Instagram dan Branding Dalam Meningkatkan Keunggulan Kompetitif Destinasi Wisata Halal Makam Syaichona Moh Cholil Bangkalan - Zuhdi, Qonita Zahira; Syarif, Muh (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The development of information and communication technology has transformed the marketing landscape, including in the tourism sector. Instagram and Branding have become important instruments for promoting tourist destinations and enhancing their competitiveness. Makam Syaichona Moh Cholil Bangkalan, as one of Indonesia's leading religious tourism destinations, has great potential for further development through the implementation of effective instagram and branding strategies. This study aims to analyze the influence of instagram and branding on improving the competitive advantage of Syaichona Moh Cholil Bangkalan. This research uses a quantitative approach with purposive sampling technique. Data will be collected through questionnaires to visitors and tourism managers. Data analysis will be conducted using multiple linear regression to test the influence of independent variables (instagram and branding) on the dependent variable (competitive advantage). The results of this study are expected to contribute scientifically to the development of religious tourism in Indonesia, especially in the context of the application of digital marketing and branding, and to provide recommendations for the managers of Makam Syaichona Moh Cholil Bangkalan in improving competitiveness and attracting more visitors.